Strategi Pengelolaan Event, Sponsorhip Dan Patnership Serta Konten Media Sosial Pada PT. Telkomsel Surabaya - Visi Ari Pratiwi; Yanda Bara Kusuma (Journal of Management and Social Sciences, 2024)
PT Telekomunikasi Indonesia Tbk is a company that provides network services. PT Telkomsel Surabaya oversees several card products, namely Telkomsel Postpaid Card, Telkomsel Prepaid Card, and By.U Card. In addition, they also offer modem products such as Orbit and Indihome as part of their sales portfolio. Direct selling is one of the most frequently used promotional and marketing methods by Telkomsel, including organizing events and collaborating with various events through sponsorship and partnerships. This research is written using a descriptive method, analyzing the results directly from the company during the internship period.